Identificación de las características virales en la implementación de campañas publicitarias en las redes sociales - Tobar Ortiz, Angelica Beatriz (2017)
The objective of this project is to identify the viral characteristics in the implementation of advertising campaigns on the social network Facebook of two fast food brands such as KFC and Pizza Hut, taking as a study an advertising piece of each one for its subsequent comparative analysis. This is a contribution to systematization of the creative processes to reach a level of sustainable virality in digital advertising, using a mixed methodology to support the theories necessary to sustain this study, yielding as results characteristics of advertising pieces considered viral and their levels of impact, proposing solutions and corrective chords for the activation of characteristics that were taken from the model initially proposed by Berger and Milkman finally hosted by Paús and Macchia who propose a more established model for the identification of content characteristics viral…….